Where was Patrick Henry on the 29th of May? - Fritz, Jean.; Tomes, Margot (New York : Coward, McCann & Geoghegan, 1975)
A brief biography of Patrick Henry tracing his progress from planter to statesman.
Wilson's Children.
Elem. School Library Collection.
School Library Journal.
4.2
3-6
Keywords: Henry, Patrick, -- 1736-1799 -- Juvenile literature; Henry, Patrick, -- 1736-1799.; Henry, Patrick, -- 1736-1799.; Statesmen; Statesmen -- United States -- Biography; Integrated Ed -- Language arts -- Upper elementary; Statesmen -- Biography; United States -- History -- Revolution, 1775-1783.; United States -- History -- 1775-1783, Revolution -- Biography